Scoping review protocol on the health of sub-Saharan African migrants in the Asia-Pacific region - Dan Wu; Yan Guo; Weiming Tang; Cheng Wang; Fan Yang; Xinkun Han; Joseph D. Tucker; Yumeng Song; Adams B. Bodomo (BMJ Open)
Introduction Increasing economic opportunities have attracted people from sub-Saharan Africa to migrate to the Asia-Pacific region in the last two decades. The information on the health situation of these migrants is limited. We aim to assess scientific evidence on the health of sub-Saharan African migrants in the Asia-Pacific region using a scoping review.Methods and analysis The review will be conducted according to the JBI guide on evidence synthesis, and the final results will be organised and reported in line with the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for scoping reviews. Search strategies have been developed centred on population-concept-context elements including sub-Saharan Africa, Asia-Pacific, migration and health. A total of eight databases will be searched, including PubMed, Embase, Cumulative Index to Nursing and Allied Health Literature, ProQuest, Scopus, Web of Science, Wanfang and CNKI. Title and abstract screening and full-text screening will be conducted by two researchers independently. Data will be charted according to predesigned form.Ethics and dissemination This study involves neither human participants nor unpublished secondary data. Institutional review board approval is therefore not required. Findings of this scoping review will be disseminated through publication in a peer-reviewed journal, through academic network and project report.